Detecting drug resistance in pancreatic cancer organoids guides optimized chemotherapy treatment. Issue 5 (5th May 2022) - Hennig, Alexander; Baenke, Franziska; Klimova, Anna; Drukewitz, Stephan; Jahnke, Beatrix; Brückmann, Sascha; Secci, Ramona; Winter, Christof; Schmäche, Tim; Seidlitz, Therese; Bereuter, Jean‐Paul; Polster, Heike; et al.
Abstract: Drug combination therapies for cancer treatment show high efficacy but often induce severe side effects, resulting in dose or cycle number reduction. We investigated the impact of neoadjuvant chemotherapy (neoCTx) adaptions on treatment outcome in 59 patients with pancreatic ductal adenocarcinoma (PDAC). Resections with tumor‐free margins were significantly more frequent when full‐dose neoCTx was applied. We determined if patient‐derived organoids (PDOs) can be used to personalize poly‐chemotherapy regimens by pharmacotyping of treatment‐naïve and post‐neoCTx PDAC PDOs. Five out of ten CTx‐naïve PDO lines exhibited a differential response to either the FOLFIRINOX or the Gem/Pac regimen. NeoCTx PDOs showed a poor response to the neoadjuvant regimen that had been administered to the respective patient in 30% of cases. No significant difference in PDO response was noted when comparing modified treatments in which the least effective single drug was removed from the complete regimen. Drug testing of CTx‐naïve PDAC PDOs and neoCTx PDOs may be useful to guide neoadjuvant and adjuvant regimen selection, respectively. Personalizing poly‐chemotherapy regimens by omitting substances with low efficacy could potentially result in less severe side effects, thereby increasing the fraction of patients receiving a full course of neoadjuvant treatment. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.